Road Improvement: Reconditioning of Gutierrez Street in Paraná - Mussin, Nahuel; Borghello, Máximo; Vitale, Simón (My University, 2023)
Summary— Paraná is a city located in Entre Ríos, Argentina, and it has many problems related to its streets. There are problems like bad lighting, poor use of space, the lack of traffic lights, and potholes. Gutierrez Street, which is a crucial artery for the city, has too many potholes that put people at risk for serious inconvenience and safety issues. The aim of this presentation is to address the potholes problem on Gutierrez Street in Paraná. The solution to this problem is to recondition the infrastructure of the road. The presentation is organized as follows. First, the problem is defined by providing information about the context where the problem is located, the description of the problem and the most specific areas where the problem is most visible. Secondly, the analysis of the problem is conducted. In this part, the causes and consequences of the problem are discussed. Thirdly, a possible solution for the problem is described as well as the advantages and disadvantages of this solution are addressed. The work's impact on Paraná can be significant. The city has a lot of street problems which lead to inconvenience and safety issues. This presentation addresses the pothole problem with an innovative road infrastructure reconditioning solution that can be replicated in other areas of the city. This solution aims to improve transportation infrastructure, safety and residents' quality of life.

Resumen— Paraná es una ciudad ubicada en Entre Ríos, Argentina, y tiene muchos problemas relacionados con sus calles. Hay problemas como mala iluminación, mal uso del espacio, falta de semáforos, y pozos. Calle Gutiérrez, la cual es una arteria crucial para la ciudad, tiene demasiados pozos que ponen a las personas en riesgo de sufrir graves inconvenientes y problemas de seguridad. El objetivo de esta presentación es abordar el problema de los pozos sobre calle Gutiérrez en Paraná. La solución a este problema es reacondicionar la infraestructura de. La presentación está organizada de la siguiente manera. En primer lugar, se define el problema proporcionando información sobre el contexto donde está ubicado el problema, la descripción del problema y las áreas más específicas donde el problema es más visible. En segundo lugar, se analiza el problema. En esta parte se discuten las causas y consecuencias del problema. En tercer lugar, se describe una posible solución para el problema, así también como las ventajas y desventajas de esta solución. El impacto de este trabajo puede ser significativo en Paraná. La ciudad tiene muchos problemas en las calles que derivan en inconvenientes y problemas de seguridad. Esta presentación aborda el problema de los pozos con una innovadora solución de reacondicionamiento de infraestructura de esta calle que puede ser replicada en otras áreas de la ciudad. Esta solución pretende mejorar la infraestructura de transporte, la seguridad y la calidad de vida de los residentes.
Keywords: Inglés I, heavy traffic, potholes, roads, road safety.; Inglés I, tráfico pesado, pozos, calles, seguridad vial.